Predictors of Kidney Function Outcomes and Their Relation to SGLT2 Inhibitor Dapagliflozin in Patients with Type 2 Diabetes Mellitus Who Had Chronic Heart Failure - Berezina, T. A.; Fushtey, I. M.; Berezin, A. A.; Pavlov, S. V.; Berezin, A. E.; Фуштей, Іван Михайлович; Павлов, Сергій Васильович (My University, 2024)
Introduction: Sodium-glucose cotransporter 2 inhibitors (SGLT2i) have a favorable impact on the kidney function in patients with heart failure (HF), while there is no clear evidence of what factors predict this effect. The aim of the study was to identify plausible predictors for kidney function outcome among patients with HF and investigate their association with SGLT2i. Methods: We prospectively enrolled 480 patients with type 2 diabetes mellitus (T2DM) treated with diet and metformin and concomitant chronic HF and followed them for 52 weeks. In the study, we determined kidney outcome as a composite of C 40% reduced estimated glomerular filtration rate from baseline, newly diagnosed end-stage kidney disease or kidney replacement therapy. The relevant medical information and measurement of the biomarkers (N-terminal natriuretic pro-peptide, irisin, apelin, adropin, C-reactive protein, tumor necrosis factor-alpha) were collected at baseline and at the end of the study.
Keywords: Heart failure; Kidney outcome; Dapagliflozin; Circulating biomarkers; Irisin; Apelin; Adropin; Natriuretic peptides